An Introduction of Cloud Computing Security and Privacy Issues in IT Industries (International Journal of Engineering and Computer Science, 2015)
Cloud Computing is a model that focuses on sharing data and computation over a scalable network. This technology has grown as promising business concept to one of the fastest growing segment of the IT industry. However, the fact that Cloud Computing offers huge opportunity to IT industry. Despite the potential gains achieved from the Cloud Computing in the organizations which are slow in accepting it due to security and privacy issues associated with it. The other aspect of Cloud Computing is that, the cost oriented IT companies are now realizing that simply by processing into the cloud they can gain fast access business applications and share their infrastructure resources at negligible cost. Regardless of the fact that cloud computing offers great advantages to the end users in which several issues that are mandatory to be addressed. It is one of the major issues which hinder the growth of cloud technology.